Hukuman Mati terhadap Narapidana Terorisme dalam Perlindungan Hak Asasi Manusia - I Putu Gde Iwan Putra Darmayatna; I Made Sepud; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2021)
Indonesia the death penalty has always been a matter of arguments because isn't based 011 the 1945 Constitution, the death penalty is in highest legal caste as the toughest punishment in the world. In this research, there are two problem formulations, namely how to regulate the death penalty against terrorism in relation to the protection of human rights and how to take legal measures against terrorism convicts to obtain legal relief. This research used the type of normative research, the techniques in the data collection are based on literature study. The results of this research indicate a conflict between the regulation of the death penalty and human rights. The regulation of the death penalty against terrorism in the relation to the protection of human rights has resulted in the emergence of various opinions and debates where the death penalty is considered to violate human rights and some consider this punishment to be applied. The effort by terrorism to obtain Juggleries a legal policy that has a basic idea i11 protecting human rights. Legal efforts to file an appeal, cassation, review to filing clemency request forgiveness from the President of the prisoners to reduce the law.